Analisis Pertimbangan Hukum Pengadilan Militer Terhadap Anggota Militer yang Menyalahgunakan Narkotika dan Psikotropika (Studi Putusan PM Nomor: PUT/17-K/PM 1-04/AD/I/2014) - Zainab Ompu Jainah (PRANATA HUKUM, 2016)
Drug abuse problem, it is already very alarming, this was due to the development of scienceand technology, as well as the impact of globalization, the current transportation is very advanced. The problem in this research is how the legal considerations of the Military Court of the Military Members who abuse Narcotic Drugs and Psychotropic? Normative juridical approach and empirical, data analysis used is qualitative. The result is the legal considerations Military Court. Although this criminal act is a special type of criminal offense, but the presumption of innocence remains to be upheld in view of the defendant are also human beings who have rights. Based on Military Justice Putuasan Number: PUT / 17-K / PM 1-04 / AD / I / 2014 which involves Yuli Basuki Rahmat sergeant demanded prison for four (4) years for the accused detained temporarily reduced and a fine of Rp 800,000,000, - ., subsidiary 2 months in jail as well as additional criminal fired from military service. Saran, the Military Court Judge is expected to be able to apply the death penalty because of the impact of this extraordinary crime that can damage the physical and mental youth.